Helicobacter infection alters the phenotype and inflammatory response of mouse intestinal muscle macrophages - Hoffman (Brogan), Sara M. (Kansas State University, 2008)
Helicobacter is a common intestinal pathogen of most laboratory mice from both commercial and academic sources worldwide. Not previously thought to have an effect, recent evidence indicates Helicobacter infection alters cytokine, chemokine, and gene expression in the stomach, intestine, and colon. Though the in vivo cell types responsible for these changes are currently unknown, in vitro results suggest macrophages are the likely source. In addition to detection and elimination of pathogens, intestinal macrophages play a role in maintaining homeostasis. By altering gene expression and cytokine production in the microenvironment, we hypothesized that Helicobacter infection altered the phenotype and inflammatory response of submucosal intestinal macrophages. To test this hypothesis, we examined macrophages within whole mounts of intestinal muscle as well as isolated macrophages from Helicobacter-infected or uninfected mouse intestine. Macrophages from the intestinal muscle of Helicobacter-infected mice showed increased expression of F4/80 and CD11b, altered gene expression, and increased phagocytosis when compared to macrophages from uninfected mice. Infection also altered the macrophage response to stimuli. Macrophages from infected mice produced significantly lower concentrations of cytokines, chemokines, and PGE[subscript]2 in response to stimulation with either IFN and LPS or IL-4 and IC. These data support our hypothesis demonstrating that the intestinal muscle macrophage phenotype, function, and response to stimulation are altered by Helicobacter infection both in vivo and in vitro.
Keywords: macrophage; Helicobacter; intestine; Biology, Microbiology (0410)